(untitled) (Journal of Health Sciences, 2015)
Introduction: In the past several decades there has been a substantial increase in the incidence of skin cancers worldwide and Croatia is no exception. The aim of this study was to estimate the financial cost of skin cancer treatment in the Osijek-Baranja County from 2000 to 2009 and to compare it with the cost of a primary prevention campaign organized in the Baranja County.Methods: We conducted a retrospective analysis of patients with skin cancer in the Baranja County and related health care costs. We designed a potential primary prevention campaign on a County level and calculated the financial expenses of campaign and then compared the results to health care costs from previous years.Results: The total cost of the treatment involving skin cancer (C43-C44) cases in the Osijek-Baranja County during the 2000-2009 periods was €483,710. The cost of a primary prevention campaign described in this study suggests that the estimated annual cost of a primary prevention campaign on the County level makes around 5.9% of the annual cost of all the medical treatment involving skin cancer patients in the County, which shows that a planned preventive approach towards the issue of skin cancer in Eastern Croatia is extremely justified and reasonable.Conclusion: The present study reveals the urgent need for the implementation of a primary prevention campaign in Eastern Croatia and puts emphasis on the economic potential of such an approach towards the problem of skin cancer.